Multifunctional Carbon Nanotubes (CNTs): A New Dimension in Environmental Remediation - Ali, Md. Eaqub; Das, Rasel; Ma'amor, Azman; Hamid, Sharifah Bee Abd (Trans Tech Publications, 2013)
Water pollution is a serious, persistent and emerging problem not only in Malaysia but all over the world. It has negative impacts on the sustainability of water resources, aquatic flora and fauna and community health. It significantly reduces total water availability because of the lack of suitable and cost-effective pollutant treatment facilities. Current facilities for water purification are time consuming, expensive and have low affinity and efficiency to newly emerging micro pollutants in water. Carbon nanotube (CNT) based nanocomposites and hybrids have attracted huge attention for their potential in the treatment of newly emerging micropollutants in water bodies. Addition of various molecules and binders such as magnetic nanoparticles, pollutant binding and degrading receptors and enzymes has added new dimensions in the fibrous shape, high aspect ratio, large surfaces, and accessible mesopores of CNTs. In this review, we have outlined the recent progress and future prospects of multifunctional CNT-hybrids for the treatment of both conventional priority and newly emerging micropollutants in water environment. The review also has highlighted the future strategies for overcoming the shortcomings of existing techniques and materials for water purification applications.